DIGESTIVE AND RESPIRATORY DISORDERS WITH INTRANUCLEAR INCLUSION BODIES IN TWO CALVES - ΠΑΠΑΔΟΠΟΥΛΟΣ, Χ.; ΣΙΜΟΣ, Ε. (Journal of the Hellenic Veterinary Medical Society, 1974)
The authors give a cytological description of liver and kidneys from two cal ves with digestive and respiratory troubles. Characteristic spherical nuclear inclusions were noticed. In one calf nuclear inclusion were noticed. In the other calf acidophilic nuclear inclusions were found in the kidneys •capillary endothelium especially in the cortex and partial vacuolated degeneration in the myocardial fibres.